Lightning surge on the DC and AC side of solar PV system - Zaini N.H.; Ab-Kadir M.Z.A.; Radzi M.A.M.; Azis N.; Ahmad N.I.; Nasir M.S.M.; Izadi M.; Ab Aziz N.F.; Ali Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Actinium; Lightning protection; Inverter; Lightning currents; Solar PVs; Striking point; Transient voltage; Electric inverters